Escape of Housekeepers at Arab Gulf Countries: Analytical Theory Study - Aldhuhoori, Mariam; KAOUACHE, Raouf (Al-Adab Journal, 2024)
The Current research attempts to analyze the theoretical and emperical knowledge about housekeepers escape at Arab gulf societies by addressing factors and consequences of the phenomenon. The housekeepers escape in Gulf countries becames an important issue since its wide spread in the last decades, and the multiple and complex problems that need to analyse in order to limit its negative impacts. An Analytical Descriptive Approach has been adopted in the identification of various factors that lead to the problem. Indeed, many theoretical approaches have been attempted to understand the process of escape. Certain Theories of Sociology, for example, have been focusing on the role of Social Construction, Non-Normality, in addition to Conflict of principles & values ​​of individuals when dealing with this phenomenon. On the other hand, Social rocesses Thteories have attributed the problem to explicit factors, such as Circumstances, and others implicit through processes of simulation and imitation to escapes carried out by specific housekeepers.Theories of Social Control have based on the availability of opportunity to escape, being satisfied with the benefits obtained from other employers, in addition to external pressures, pushing for escape from domestic work. We should note, that conclusions of previous studies have showed that escape of housekeepers can be traced to mistreatment in general, like being not allowed for instance to take a break, or undermined with their basic rights, including housing, food, appropriate clothes, and delay of wages. Besides, some housekeepers might not be inclined to work according to the concluded contract, and encouraged sometimes by Recruitment Agencies, especially if they are females, for escape after the end of Probationary Period. We are obliged to note as well that there are individuals, families and companies who could benefit from the escape of housekeepers all along with gangs that organize and manage Prostitution Networks and other Crimes.